Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Toko Retail WN Telang Pada Mahasiswa - Camelia; Nurita Andriani (JURNAL ECONOMINA, 2024)
This research analyzes the influence of price and service quality on customer satisfaction at the WN Telang Store, Madura, using quantitative methods with 60 student respondents from Trunojoyo University, Madura. The results of multiple linear regression analysis carried out with SmartPLS 4 software show that price has a significant effect on customer satisfaction, while service quality does not show a significant effect. These findings suggest that although competitive prices attract customers, service quality remains important for a satisfying shopping experience. This research recommends shop owners to increase friendliness and attention in service to increase customer satisfaction and loyalty.